2020
DOI: 10.3390/agronomy10020263
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Tomato as a Tool to Improve Salt Tolerance

Abstract: Salinity in soil or water is a serious threat to global agriculture; the expected acreage affected by salinity is about 20% of the global irrigated lands. Improving salt tolerance of plants through breeding is a complex undertaking due to the number of traits involved. Grafting, a surgical mean of joining a scion and rootstock of two different genotypes with the desired traits, offers an alternative to breeding and biotechnological approaches to salt tolerance. Grafting can also be used to circumvent other bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 115 publications
0
46
0
4
Order By: Relevance
“…Grafting has resulted in enhanced fruit quality and yield in many vegetables, such as tomato [9][10][11], watermelon, cucumber, melon, capsicum and eggplant [12,13]. Increased nutrient uptake [14], and enhanced tolerance to abiotic stresses, such as extreme temperatures [4,14,15], salinity [13,16], alkalinity [17], drought [6,18], flooding [19] and heavy metals [9,20] was also seen in grafted plants.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting has resulted in enhanced fruit quality and yield in many vegetables, such as tomato [9][10][11], watermelon, cucumber, melon, capsicum and eggplant [12,13]. Increased nutrient uptake [14], and enhanced tolerance to abiotic stresses, such as extreme temperatures [4,14,15], salinity [13,16], alkalinity [17], drought [6,18], flooding [19] and heavy metals [9,20] was also seen in grafted plants.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that grafting vegetable crops onto tolerant rootstocks can improve global plant performance and final productivity under different abiotic stress conditions [ 10 , 11 , 13 , 14 , 15 , 16 ]. Particularly, improved growth and yield stability responses mediated by the rootstock under salinity conditions have been described in different vegetable crops, such as tomato [ 17 , 18 , 19 , 20 ], pepper [ 21 , 22 , 23 , 24 ], cucumber [ 25 , 26 ], watermelon [ 27 ], and others [ 28 ]. These rootstock-mediated responses have been associated with a better status of the photosynthetic apparatus and increased sink activity [ 8 , 22 ], regulation of ion homeostasis [ 17 , 20 , 21 , 26 ], and modulation of hormonal balance [ 14 , 17 , 18 , 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…O tomate (Solanum lycopersicum) tem destaque no cenário agrícola mundial, com aptidão para consumo fresco ou processado. Os frutos, com grande popularidade e volume consumido, servem como uma importante fonte de nutrientes em dietas contemporâneas (BREKSA et al, 2015), que possui propriedades antioxidantes e anticâncer (GERSZBERG; HNATUSZKO-KONKA, 2017) com significância econômica (SINGH et al, 2020). O Brasil é um dos maiores produtores de tomate para processamento no mundo.…”
Section: Introductionunclassified